2015
DOI: 10.4049/jimmunol.1402540
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy Using IL-2/IL-2 Monoclonal Antibody Complexes, Rapamycin, and Islet Autoantigen Peptides Increases Regulatory T Cell Frequency and Protects against Spontaneous and Induced Type 1 Diabetes in Nonobese Diabetic Mice

Abstract: Regulatory T cells (Treg) play a crucial role in the maintenance of self-tolerance. In this study, we sought to expand Ag-specific Tregs in vivo and investigate whether the expanded Tregs can prevent or delay the development of type 1 diabetes (T1D) in the NOD mouse model. NOD mice were treated with a combination of IL-2/anti–IL-2 Ab complex, islet Ag peptide, and rapamycin. After the combined treatment, CD4+CD25+Foxp3+ Tregs were significantly expanded in vivo, they expressed classical Treg markers, exerted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 52 publications
3
28
1
2
Order By: Relevance
“…A combinational therapy has also been assessed with the use of IL-2/anti-IL-2 Ab complexes in combination with rapamycin and islet antigen peptide treatment. T reg expansion was observed and mice protected from diabetes development in both spontaneous and induced models of diabetes (43). …”
Section: Boosting Tregs In Mice and Humansmentioning
confidence: 99%
“…A combinational therapy has also been assessed with the use of IL-2/anti-IL-2 Ab complexes in combination with rapamycin and islet antigen peptide treatment. T reg expansion was observed and mice protected from diabetes development in both spontaneous and induced models of diabetes (43). …”
Section: Boosting Tregs In Mice and Humansmentioning
confidence: 99%
“…Besides, studies have also shown that Tregs in subjects with T1D has defects in their immunosuppressive function . Tregs, especially beta cell‐specific Tregs have been shown to preserve the beta cell mass, delay progression of diabetes and have been explored during the past few years for cellular therapy of T1D . To the best of our knowledge, this is first report that shows the characteristics of islet‐associated (PI‐specific) Tregs in human subjects with T1D.…”
Section: Discussionmentioning
confidence: 88%
“…12,42 Tregs, especially beta cell-specific Tregs have been shown to preserve the beta cell mass, delay progression of diabetes and have been explored during the past few years for cellular therapy of T1D. [43][44][45][46][47] To the best of our knowledge, this is first report that shows the characteristics of islet-associated (PI-specific) Tregs in human subjects with T1D. In this study, we first observed a higher frequency of polyclonal Tregs in AOT1D subjects with better preservation of beta cell mass that had a positive correlation with age.…”
Section: Discussionmentioning
confidence: 99%
“…A phase I trial focused on use of rapamycin and IL-2 in an effort to boost Treg function in recent-onset T1D, and the use of this combination was based on strong preclinical data suggesting modulation of multiple aspects of T1D pathogenesis in mouse studies (73, 74). Rapamycin is routinely used during organ transplantation and blocks the mammalian target of rapamycin complex 1 (mTORc1), which is an important regulator of cell cycle progression (75).…”
Section: Combination Immunotherapiesmentioning
confidence: 99%